Pengembangan Sistem Keamanan berbasis Cloud dengan Analisis Efek Avalanche pada Jaringan Perusahaan yang Mengadopsi Infrastruktur Cloud - Fauzan Prasetyo Eka Putra; Fahri Khusaini; Amsori Amsori; Khoirul Anam (Pusat Riset dan Inovasi Nasional, 2025)
By adding cloud infrastructure to the company's network, there are new challenges for data security, especially related to the increasing possibility of complex cyberattacks.The main weakness of traditional systems is their inability to detect small changes in data, which can lead to data breaches.The purpose of this article is to build a cloud-based network defense system that utilizes avalanche effect analysis to enhance anomaly detection.Cryptographic algorithms with high avalanche effects are used in the simulation of cloud-based corporate networks in this study.After simulating attacks on the tested system, data is collected and then analyzed to evaluate the effectiveness and sensitivity of detection.To conduct validation tests, metrics such as detection accuracy and response time are used to compare the system's performance with conventional methods.The research results show that the use of algorithms with significant avalanche effects can enhance the system's ability to detect small suspicious changes in data, thereby reducing the likelihood of hidden attacks.The results show that adding avalanche features to the cloud defense system can enhance the company's network defense against current threats.Additionally, it has been proven that the developed system enhances operational efficiency without compromising network performance.To enhance adaptation to new attack patterns and test the system on a real implementation scale, further research must be conducted.